Coding in medically assisted reproduction: the status of the implementation of the Single European Code for reproductive cells and tissues. Issue 3 (15th July 2020) - ,; Alteri, Alessandra,; Vermeulen, Nathalie; Rugescu, Ioana Adina; Nogueira, Daniela; Veleva, Zdravka; D'Angelo, Arianna; Tilleman, Kelly
Abstract: STUDY QUESTION: To evaluate the implementation of the coding systems in medically assisted reproduction (MAR) centres in the European Union (EU). SUMMARY ANSWER: Our data show that a significant number of MAR centres use the Single European Code (SEC), but it also shows certain limitations to the coding. WHAT IS KNOWN ALREADY: Traceability and identification of tissue and cells used for clinical application are extremely important as it is one of the key aspects of quality and safety both for the donors and the recipients. Patients as well as tissues and cells move across the European continent and far beyond, hence a uniform coding system was very much needed. The coding of tissues and cells from human origin was already embedded in the EU directives 2004/23/EC. The use of the Single European Code (SEC) on tissues and cells was enforced in 2017 for tissues and cells distributed within the EU or exported from the EU. The SEC ensures standardization within the EU, allowing the integration of the two existing codes (ISBT-128 and Eurocode) within the SEC structure. Likewise, in the MAR field, the SEC was launched in order to ensure the traceability of reproductive tissues and cells. Gametes and embryos from partner donation as well as reproductive cells and tissues of allogeneic donation were excluded from the SEC as long as they remain in the centre of origin. STUDY DESIGN, SIZE, DURATION: A cross-sectional survey aimed to gain insight into the use of SEC by MAR centres was conducted between 5 November and 15 December 2018. PARTICIPANTS/MATERIALS, SETTING, METHODS: The online survey was distributed among the ESHRE members. MAIN RESULTS AND THE ROLE OF CHANCE: The survey results highlight the strengths and weaknesses in the practical use of the SEC. The data from the survey showed that the SEC code is something that is known in the MAR field. Our data showed that over half of the respondents were using the SEC in their centre. On the other hand, there is also criticism about the use of SEC in MAR, especially that the added value for traceability and identification in ART is found to be rather limited. LIMITATIONS, REASONS FOR CAUTION: The survey response rate was rather low (4.84%). The view of the use of SEC discussed in this paper still provides insight into the use of the SEC in several MAR centres. WIDER IMPLICATIONS OF THE FINDINGS: The survey highlights some knowledge gaps concerning coding. This information can be used to develop tools to increase knowledge of the SEC. STUDY FUNDING/COMPETING INTEREST(S): There was no external funding for this study. The authors declare that they have no conflict of interest. TRIAL REGISTRATION NUMBER: N/A.